The Sensor Proteins BcSho1 and BcSln1 Are Involved in, Though Not Essential to, Vegetative Differentiation, Pathogenicity and Osmotic Stress Tolerance in Botrytis cinerea - Ren, Weichao; Liu, Na; Yang, Yalan; Yang, Qianqian; Chen, Changjun; Gao, Qingli (Frontiers in Microbiology, 2019)
High-osmolarity glycerol (HOG) signaling pathway belongs to mitogen-activated protein kinase (MAPK) cascades that regulate responses of organism to diverse extracellular stimuli. The membrane spanning proteins Sho1 and Sln1 serve as biosensors of HOG pathway in Saccharomyces cerevisiae. In this study, we investigated the biological functions of BcSHO1 and BcSLN1 in the gray mold fungus Botrytis cinerea. Target gene deletion demonstrated that both BcSHO1 and BcSLN1 are important for mycelial growth, conidiation and sclerotial formation. The BcSHO1 and BcSLN1 double deletion mutant ΔBcSln1-Sho1 produced much more, but smaller sclerotia than ΔBcSho1 and the wild-type (WT) strain, while ΔBcSln1 failed to develop sclerotia on all tested media, instead, formed a large number of conidia. Infection tests revealed that the virulence of ΔBcSln1-Sho1 decreased significantly, however, ΔBcSho1 or ΔBcSln1 showed no difference with the WT strain. In addition, ΔBcSln1-Sho1 exhibited resistance to osmotic stress by negatively regulating the phosphorylation of BcSak1 (yeast Hog1). All the phenotypic defects of mutants were recovered by target gene complementation. These results suggest that BcSHO1 and BcSLN1 share some functional redundancy in the regulation of fungal development, pathogenesis and osmotic stress response in B. cinerea.